IMPLIKASI HUKUM PERDATA DALAM PENANGANAN KASUS KETERLAMBATAN LAYANAN POLISI : PERSPEKTIF PERLINDUNGAN HAK WARGA NEGARA INDONESIA - Jowan (SCIENTIA JOURNAL, 2024)
This study looks into the legal implications of police service delays under civil law, with an emphasis on protecting Indonesian residents' rights. Delays in police services can have serious consequences for citizens' rights and safety, necessitating a thorough investigation of the legislative structure controlling such situations. This study aims to highlight the rights afforded to Indonesian residents in circumstances of delayed police response, as well as the legal remedies available to them, by a review of relevant civil laws and regulations. By performing a detailed investigation of legal provisions and case studies, this article attempts to provide insights into the successful utilization of the civil law system to defend citizens' rights and provide timely and efficient